Undergraduates as Researchers - the Impact of Active Participation in Research and Conference Presentation on Psychology Undergraduate Identity and Career Aspirations - Janis McIntyre Davidson; Minna Lyons (Edinburgh Napier University in collaboration with Aston University, the Universities of Dundee and Auckland, 2018)
Although research-led teaching has been identified as an important part of psychology curricula in the United Kingdom, less is known about the impact of undergraduate research collaborations with academics, culminating in a conference presentation. The present study was a qualitative investigation into the experience of student-staff collaboration from a student perspective. We conducted semi-structured interviews with five psychology students who worked together with staff conducting research during their undergraduate degrees, disseminating the findings at an academic conference. The interviews were analysed using a thematic approach. We identified three themes, which were around the relationship with their tutor, career aspirations, and identity as a researcher/psychologist. Overall, the interviews indicated that undertaking research and attending academic conferences has a positive impact on future career aspirations, and helps students to feel that they are part of an academic community. Academic staff teaching in research-led psychology programmes should consider giving students opportunities to immerse themselves fully in the research process, ideally leading to a conference presentation for academic audiences.